Perancangan Sistem Business Intelligence Pada Data Perusahaan FNB X (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Nowadays, the use of technology as a tool for the success of a business has become very common. Sales and purchase transactions of a business are carried out using the latest technology that can make all transactions recorded on the system. However, in fact, the data is only a small thing in determining the success or decision-making of the leader of a company. By designing a system that can change business information from existing operational data, it can ultimately provide support for business decisions for company leaders.